Steering System Kinematic and Steady-State Cornering Analyses of the ITS Electric Car - Unggul Wasiwitono; Indra Sidarta; Agus Sigit Pramono; Sutikno Sutikno; Alief Wikarta (IPTEK Journal of Proceedings Series, 2014)
Steering linkages play an important role in maneuvering of cars. In order to provide pure rolling of the road wheels and to reduce wear of the tires, the steering linkage must be able to turn the wheels such that their axis intersection point lies on the rear wheel axis. This condition is known as the Ackermann condition. However, in reality, Ackermann condition is difficult to satisfy for every cornering radius. The only effort we can do is to synthesize the linkage so that the Ackermann condition is satisfied for any turning radius as closely as possible. Hence, an appropriate kinematic model of the steering linkage is essential. The purpose of this research is to analyze the rack and pinion steering linkage for the ITS electric car prototype. From this analysis, the information on the steering linkage dimension and the placement of the steering linkage that give minimum steering error can be obtained. The steering error is defined as the difference between the actual angle made by the outer front wheel during steering maneuvers and the correct angle for the same wheel based on the Ackerman principle. In addition, the steady-state cornering behavior analysis is also conducted. From this analysis, the information of the center of gravity location that give better cornering characteristics can be obtained. Therefore, these analyses help and can be used as starting point to design the chassis and cabin for the ITS electric car prototype.